Protection from infection and reinfection due to the Omicron BA.1 variant in care homes - Choudhry, Saher; Rowland, Thomas A. J.; McClelland, Kamil; Renz, Erik; Iyanger, Nalini; Chow, J Yimmy; Aiano, Felicity; Ladhani, Shamez N.; Jeffery-Smith, Anna; Andrews, Nick J.; Zambon, Maria (Frontiers in Immunology, 2023)
Prospective longitudinal surveillance of nine sentinel London care homes from April 2020 onwards found that all experienced COVID-19 outbreaks due to Omicron (BA.1) during December 2021 and January 2022, despite extensive previous SARS CoV 2 exposure and high COVID-19 vaccination rates, including boosters (>70% residents, >40% staff). Detailed investigation showed that 46% (133/288) of Omicron BA.1 infections were SARS CoV 2 reinfections. Two and three COVID-19 vaccines doses were protective against Omicron infection within 2-9 weeks of vaccination, though protection waned from 10 weeks post-vaccination. Prior infection provided additional protection in vaccinated individuals, approximately halving the risk of SARS-CoV-2 infection. Anti-S antibody titre showed a dose-dependent protective effect but did not fully account for the protection provided by vaccination or past infection, indicating that other mechanisms of protection are also involved.